ТЕХНОЛОГІЧНІ АСПЕКТИ ФОРМУВАННЯ ДОСВІДУ ЦІЛІСНОГО ПІЗНАННЯ МУЗИЧНИХ ЯВИЩ (Педагогіка вищої та середньої школи, 2007)
In article problems of adequate understanding of the musical contents are considered. Artlycognitive opportunities of the style approach are covered, mechanisms of judgement of the musical-style phenomena are opened, the expediency of introduction of style bases in musical-student teaching is proved,